Large-Scale Transcriptome Analysis of Retroelements in the Migratory Locust, Locusta migratoria - Jiang, Feng; Yang, Meiling; Guo, Wei; Wang, Xianhui; Kang, Le (PloS one, 2012)
Retroelements can successfully colonize eukaryotic genome through RNA-mediated transposition, and are considered to be some of the major mediators of genome size. The migratory locust Locusta migratoria is an insect with a large genome size, and its genome is probably subject to the proliferation of retroelements. An analysis of deep-sequencing transcriptome data will elucidate the structure, diversity and expression characteristics of retroelements. We performed a de novo assembly from deep sequencing RNA-seq data and identified 105 retroelements in the locust transcriptome. Phylogenetic analysis of reverse transcriptase sequences revealed 1 copia, 1 BEL, 8 gypsy and 23 non-long terminal repeat (LTR) retroelements in the locust transcriptome. A novel approach was developed to identify full-length LTR retroelements. A total of 5 full-length LTR retroelements and 2 full-length non-LTR retroelements that contained complete structures for retrotransposition were identified. Structural analysis indicated that all these retroelements may have been activated or deprived of retrotransposition activities very recently. Expression profiling analysis revealed that the retroelements exhibited a unique expression pattern at the egg stage and showed differential expression profiles between the solitarious and gregarious phases at the fifth instar and adult stage. We hereby present the first de novo transcriptome analysis of retroelements in a species whose genome is not available. This work contributes to a comprehensive understanding of the landscape of retroelements in the locust transcriptome. More importantly, the results reveal that non-LTR retroelements are abundant and diverse in the locust transcriptome.